Follow up of growth, development and clinical outcome in neonates discharged from the NICU of tertiary care hospital in central India - C., Prithvichandra K.; Ghanghoriya, Pawan K. (International Journal of Contemporary Pediatrics, 2020)
Background: To assess the growth and neurodevelopmental outcome of all newborn discharged from the NICU of Netaji Subhash Chandra Bose Medical College, Jabalpur on follow up for 6 months. Methods: Prospective observational cohort study of 200 high risk newborn discharged from NICU. Babies were called for follow up at 1 month, 2 months, 4 month and 6 months of corrected age and detailed information was taken regarding NICU stay and morbidity with the help of data available from discharge card. Anthropometric parameters like weight, length, and head circumference were noted. Suitable screening tests like denver’s developmental screening test for Indian infants (DDSTII) for NDD (neurodevelopmental delay) and Amiel Tison scoring for tone assessment was done. Results: Among the 200 NICU graduates chosen, 40 lost during follow up. The neurodevelopmental delay in this study was 31.3%. Authors also analysed NDD according to gestational age wise groups. NDD in pre-terms was 39.6%. The developmental delay was more in babies with neonatal sepsis, perinatal asphyxia, prematurity, RDS, NEC etc. Conclusions: The morbidities like severe perinatal asphyxia, hypoglycaemia, seizures, shock, hypoxia, hypothermia, low gestational age have direct association with NDD.